Oxygen Nonstoichiometry and Electrochemical Properties of LaNiO3-δ. (13th April 2015) - Budiman, Riyan Achmad; Hashimoto, Shin-ichi; Nakamura, Takashi; Yashiro, Keiji; Amezawa, Koji; Kawada, Tatsuya
Abstract : The chemical stability and electrochemical properties of LaNiO3-δ was measured by various temperature and oxygen partial pressure p (O2). The chemical stability of LaNiO3-δ has been determined by coloumetric titration and high temperature X-ray diffraction (XRD). The LaNiO3-δ has a short range of chemical stability over the p (O2 ). At the high temperature and low p (O2 ) (10 -4 bar) the XRD patterns shows the NiO peaks, where the Ni 3+ reduce into Ni 2+ . On the other side, the study on the electrochemical impedance spectroscopy indicates that it has relatively high area specific conductivity, although it has short range chemical stability over the p (O2 ).